1991
DOI: 10.1152/ajpendo.1991.260.2.e194
|View full text |Cite
|
Sign up to set email alerts
|

Pathway and carbon sources for hepatic glycogen repletion in dogs

Abstract: The present studies were undertaken to quantitate the relative contributions of the indirect and direct pathways for hepatic glycogen repletion and to determine the role of splanchnic tissues in provision of C precursors used for the indirect pathway. For this purpose, we administered oral glucose (1.4 g/kg) enriched with [1-14C]glucose to 18-h fasted dogs and measured net hepatic and net gastrointestinal glucose, lactate, and alanine balance, hepatic and gastrointestinal fractional extraction [( 3H]lactate), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…With the direct pathway, glycogen is formed from glucose 6-phosphate originating from glucose taken up and phosphorylated within the liver and then directly incorpor-ated into glycogen whereas with the indirect pathway, glycogen is formed from glucose 6-phosphate originating from gluconeogenic precursors generated either within the liver or extrahepatic tissues [10,11]. In vitro studies and experiments in rats have generally indicated that the indirect pathway is the major route for glycogen synthesis [9] but their validity and physiologic significance have been questioned [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the direct pathway, glycogen is formed from glucose 6-phosphate originating from glucose taken up and phosphorylated within the liver and then directly incorpor-ated into glycogen whereas with the indirect pathway, glycogen is formed from glucose 6-phosphate originating from gluconeogenic precursors generated either within the liver or extrahepatic tissues [10,11]. In vitro studies and experiments in rats have generally indicated that the indirect pathway is the major route for glycogen synthesis [9] but their validity and physiologic significance have been questioned [8].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this assumption, the studies of Radziuk [14] and Jackson et al [25] indicate that absorption of ingested glucose would be complete by 4.5-5 h. Furthermore, the data of Jackson et al [25], Mitrakou et al [10], and Kelley et al [24] indicate that at least 80 % of the ingested glucose would have been removed from plasma within 5 h of its ingestion. Given a half-life in plasma of 44.4 min for glucose [25], it can be calculated that less than 0.15 % of the last ingested glucose load would not have been removed from plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After oral glucose ingestion in the healthy human, 50 -77% of the liver glycogen synthesized is derived via the direct pathway (3)(4)(5)(6). The response of the conscious dog is similar to that of humans, with 25-40% of a gastrointestinal glucose load being taken up by the liver and 50 -62% of accumulated hepatic glycogen being synthesized via the direct pathway (7)(8)(9).…”
mentioning
confidence: 81%
“…In the dog, arterial plasma glucose levels of 160-290 mg/dl and insulin levels of 35-384 U/ml resulted in rates of NHGU of 1.0-2.9 mg/kg/min (1). These results demonstrate that the combination of hyperinsulinemia and hyperglycemia cannot account for the peak rates of NHGU (up to 7.5 mg/kg/min) present after the ingestion of glucose in either humans or the dog (1,(4)(5)(6)(7)(8)(9). In addition to the rise in insulin and glucose, meal ingestion also produces a rise in the portal vein glucose level that is greater than the glucose level in the arterial circulation.…”
Section: Introductionmentioning
confidence: 87%